Design Of Tourism Area Development Siteplan in Rabi Jonggor District, Mountain Tuleh District Pasaman Barat District, West Sumatra Province (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
Kenagarian Rabi Jonggor, Gunung Tuleh District, West Pasaman Regency, West Sumatra Province, has various natural potentials that can be developed to become a tourist and research destination for academics. Potential hot springs containing minerals such as sulfur can be found at several points in the Jorong Sitabu Kenagarian Rabi Jonggor area, Gunung Tuleh District, West Pasaman Regency. The hot springs in Jorong Sitabu Kenagarian Rabi Jonggor, Gunung Tuleh District, West Pasaman Regency originate from a meeting between groundwater and magma in a magma chamber in a volcanic path. Some of these hot springs have been used as hot springs and some have not been developed into hot springs. Added to this is the existence of a living sea lake which is currently viral on social media, which makes nature lovers curious to come to it, not to forget the panoramic view of the protected forest which really spoils the eye, which is termed the heaven of West Pasaman. Infrastructure for supporting facilities for tourism objects is not yet available in accordance with existing regulations. This potential can be developed into several hot spring baths so that later the Jorong Sitabu Kenagarian Rabi Jonggor area, Gunung Tuleh District, West Pasaman Regency can become a tourist area for tracking, hiking, camping, outbound and education. Based on the problems above, the goal to be achieved from this research is to design hot spring tourism areas, protected forests and marine lakes to live with the 3A concept. In this study a qualitative approach was used by means of field observations, interviews and literature studies. The results of this study are zoning for the development of natural tourist attractions, zoning for natural and man-made attractions, zoning for accessibility between supporting tourism objects and zoning amenities (facilities) that can be developed in order to support the achievement of a comfortable and managed tourist area in Jorong Sitabu Kenagarian Rabi Jonggor, Gunung Tuleh District, West Pasaman Regency with the problem seeking and problem solving method, then developed with AutoCAD software in the form of a Landscape Overlay, so that the results of this study produce a design based on the results of field analysis which at least is able to answer the weaknesses and deficiencies of existing facilities in this tourist area, which if realized by related parties, will indirectly improve the regional economy and help improve the quality of life of the local community.